The Effectiveness of Social Media Platforms in Boosting E-Marketing Outreach: A Field Study on Marketers in Sana’a Capital. - Sakher Farea Ghaleb Algonaid; Ayoub Qaid Naji Almaidama (Citakonsultindo, 2025)
This study investigates the The Effectiveness of Social Media Platforms in Boosting E-Marketing Outreach: A Field Study on Marketers in Sana’a Capital. Employing a descriptive-analytical methodology, the research systematically examines data collected from a Random Sample of Marketers in Sana’a Capital. Utilizing advanced statistical analysis, the findings demonstrate a statistically significant positive influence of Social Media Platforms in Boosting E-Marketing Outreach, with a measured effect size of Instagram (β = 0.422). Furthermore, the implementation of Facebook (β = 0.227) and WhatsApp (β = 0.245) also X(Twitter) (β = 0.068) was found to exert a substantial and statistically significant effect on Boosting E- marketing Outreach. The study also highlights a pronounced sector-wide shift toward Social media Platform adoption, The results indicate that Instagram is the most widely used and influential platform in e-marketing, achieving the highest mean score and relative importance, with the strongest positive effect on campaign reach. This is due to its strong visual appeal and high user engagement, particularly among younger audiences. Facebook ranks second, showing a moderate but significant effect, highlighting its continued importance as a supportive tool for reaching a broad audience despite the growing preference for Instagram. WhatsApp occupies the third position, demonstrating a positive impact through enhancing direct communication and interaction with customers, which increases the effectiveness of marketing campaigns. In contrast, X(Twitter) ranked last in usage and showed a non-significant effect, indicating its limited effectiveness in promoting e-marketing within the studied context.